2020
DOI: 10.7888/juoeh.42.307
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of GPS-attached Pocket PM2.5 Measuring Device for Personal Exposure Assessment

Abstract: Assessment of personal exposure to particulate matter with an aerodynamic diameter less than or 2.5 µm (PM2.5) is necessary to study the association between PM exposure and health risk. Development of a personal PM2.5 sensor or device is required for the evaluation of individual exposure level. In this study, we aimed to develop a small-sized, lightweight sensor with a global positioning system (GPS) attached that can measure PM2.5 and PM10 every second to assess continuous personal exposure levels. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, personal PM 2.5 exposures of 26 nonsmoking adults were studied in Taiwan using AS-LUNG-P at different indoor and outdoor microenvironments, with a 5-min average of 11.2 ± 10.9 µg/m 3 [13]. In Yangon, Myanmar, personal PM 2.5 exposures of 15 housewives and 15 university female teaching staff members were assessed to evaluate a small and lightweight LCPMS (Pocket PM 2.5 Sensors, Yaguchi Electric Co., Ltd., Miyagi, Japan) [102]. They reported that the average 24-h PM 2.5 exposure levels of housewives and female university teaching staff were 16.1 ± 10.0 µg/m 3 and 15.8 ± 4.0 µg/m 3 , respectively.…”
Section: The 24-h Personal Pm 25 Exposurementioning
confidence: 99%
“…In addition, personal PM 2.5 exposures of 26 nonsmoking adults were studied in Taiwan using AS-LUNG-P at different indoor and outdoor microenvironments, with a 5-min average of 11.2 ± 10.9 µg/m 3 [13]. In Yangon, Myanmar, personal PM 2.5 exposures of 15 housewives and 15 university female teaching staff members were assessed to evaluate a small and lightweight LCPMS (Pocket PM 2.5 Sensors, Yaguchi Electric Co., Ltd., Miyagi, Japan) [102]. They reported that the average 24-h PM 2.5 exposure levels of housewives and female university teaching staff were 16.1 ± 10.0 µg/m 3 and 15.8 ± 4.0 µg/m 3 , respectively.…”
Section: The 24-h Personal Pm 25 Exposurementioning
confidence: 99%
“…Obtaining expensive instrumentation to monitor air quality is not always foregone, especially in developing or industrializing areas, but NGMSs can solve this problem due to their low cost and easy applicability [ 76 ]. Win-Shwe et al (2020) [ 91 ] indicated that continuous assessment of personal exposure level is possible using the NGMS developed in their study, also matching NGMS with mobile sensing technologies. The authors are planning to give health education to the public regarding lifestyle in microenvironments with the scope to reduce indoor air pollution [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Win-Shwe et al (2020) [91] indicated that continuous assessment of personal exposure level is possible using the NGMS developed in their study, also matching NGMS with mobile sensing technologies. The authors are planning to give health education to the public regarding lifestyle in microenvironments with the scope to reduce indoor air pollution [91]. Barkjohn et al (2020) [73], using several NGMSs, have pointed out that reducing the infiltration of outdoor air in homes and decreasing pollution at the city or country level can reduce the personal exposure of citizens.…”
Section: Applications In Environmental Monitoring and Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviating the need for an observer will considerably reduce labor costs. The Global Navigation Satellite System (GNSS), represented by the Global Positioning System (GPS), is the standard technology for outdoor positioning [4]. However, such technologies cannot be utilized for indoor positioning because satellite signals cannot be received indoors.…”
Section: Introductionmentioning
confidence: 99%